(untitled) - Melissa Orzechowski Xavier; Laura Riffel Bittencourt; Cláudio Moss da Silva; Roseli Stone Vieira; Hugo Cataud Pacheco Pereira (Sociedade Brasileira de Medicina Tropical (SBMT), 2013)
Sporotrichosis occurs after fungal implantation of Sporothrix spp. in the skin, and is the main subcutaneous mycosis in Latin America. Here we describe three atypical cases of the disease. The first case report an extra-cutaneous occurrence of the disease with joint infection; the second one describes a patient with bilateral lymphocutaneous form of sporotrichosis; and the third shows a zoonotic cutaneous case with the development of an erythema nodosum as a hypersensitivity reaction. These cases show the disease importance on the region and the necessity of fungal culture to the diagnosis confirmation.